Spectral analysis of Rayleigh waves in south-eastern parts of Niger delta, Nigeria - Emmanuel, Aniwetalu; Juliet, Ilechukwu; Vivian, Oguadinma; Kingsley, Chiadikobi; Ezechimelu, Nnaji (International Journal of Advanced Geosciences, 2017)
Interference of ground roll energy on true seismic reflection records has continued to pose a serious challenge to exploration geophysicists. In view of this, amplitude and power spectra of the Rayleigh waves which are the precursor of the ground roll energy were derived from over 70 raw monitor records and plotted as a function of frequency. The objective is to determine the locus of ground energy in the seismic records, analyse their dispersion pattern and suggests viable ways of suppressing them. The results of the amplitude spectrum plots revealed that Rayleigh waved exhibit oscillatory behavior with very high-amplitude values, which correspond to the locus of ground roll energy. This energy is confined to very low frequency range of about 4-9Hz. The Power spectrum which was given as the square of the amplitude as a function of frequency showed appreciable lobes of breaths of the ground roll energy of about 0.5-0.7cm and their trend of dispersions. The power spectrum plots revealed several peaks excluding the early peaks that are direct indication of ground roll energy. The plots showed pronounced and constant decline in energy levels with increasing frequency and reaching very low decibel values of -60Db to -80Db at frequency range of 50Hz. This indicates that the environment is dispersive in nature which probably results from velocity layering. This is a precursor to seismic noise which among others can be suppressed in the field by designing filters with sharper cut off characteristics.